Snow White. (Paradise press, 2005)
An abridged version of the popular story of Snow White and her friendship with seven dwarfs, with color illustrations. Includes a read-along CD with music.
On board pages.
K-3.
Preschool.
Preschool
Keywords: Perseverance (Ethics) -- Juvenile fiction; Snow White (Tale) -- Juvenile fiction; Perseverance (Ethics) -- Fiction; Snow White (Tale) -- Fiction; Board books for children; Fairy tales; Perseverance -- Fiction; Snow White (Tale) -- Fiction